Does digital history need a theory? - Karcher, Stefan (Interdisciplinary forum of digital textual sciences, 2018)
Whoever has studied history has surely heard about the great controversies on historiographical theories and schools with their linguistic and epistemological ideas. It seems to me that the 20th ce…
Updated 2018-12-06
Gesehen am 29.01.2019